2000
DOI: 10.1038/sj.cdd.4400685
|View full text |Cite
|
Sign up to set email alerts
|

Increase in ultraviolet sensitivity by overexpression of calpastatin in ultraviolet-resistant UVr-1 cells derived from ultraviolet-sensitive human RSa cells

Abstract: Human RSa cells are highly sensitive to apoptotic-like cell death by ultraviolet irradiation (UV) while UV r -1 cells are their variant with an increased resistance to UV. Three days after UV at 10 J/m 2 , the viability of RSa cells was approximately 17% while that of UV r -1 cells was 65%. This different survival might reflect apoptotic cell death since apoptosis-specific DNA ladder was more clearly observed in RSa cells than in UV r -1 cells after UV. Addition of ALLN/calpain inhibitor I to the culture mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…Both RSa and XP2OS cells show high sensitivity to the lethal effect of UV. 7,34 UVAP-1 cells are also sensitive to UV lethality as well as the parent RSa cells, although they are more resistant to UV mutagenicity than RSa cells. 8 Thus, cellular susceptibility to UV lethality may not be causally related with that to nicotine-induced apoptosis among the 3 cell strains tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both RSa and XP2OS cells show high sensitivity to the lethal effect of UV. 7,34 UVAP-1 cells are also sensitive to UV lethality as well as the parent RSa cells, although they are more resistant to UV mutagenicity than RSa cells. 8 Thus, cellular susceptibility to UV lethality may not be causally related with that to nicotine-induced apoptosis among the 3 cell strains tested.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we utilized a human RSa cell strain and its derivative, the UVAP-1 cell line. RSa cells are highly sensitive to apoptosis induced by various agents 7 and were found here to be susceptible to nicotine-induced apoptosis. UVAP-1 cells were established as cells with increased levels of protease activity after UV irradiation 8 and were found here to have increased resistance to nicotine-induced apoptosis.…”
mentioning
confidence: 98%
“…We therefore suggested that an increase in antipain-sensitive protease activity by UV irradiation is involved in the suppression of cell mutability. Furthermore, we recently found that an increase in protease activity promptly after UV irradiation was associated with changes in the resistance of RSa cells (Sugita et al, 2001;Hiwasa et al, 2000). It is suggested that the increase in protease activity by UV irradiation is involved in the suppression of UV cell-killing.…”
Section: Introductionmentioning
confidence: 96%
“…After incubation with horseradish peroxidase-conjugated secondary antibody, immunoreactivity was detected with the Immobilon (Merck Millipore, Darmstadt, Germany) as previously described [18,22].…”
Section: Western Blottingmentioning
confidence: 99%